Estrogenic activity of furanocoumarins isolated from Angelica dahurica - Piao, Xiang Lan; Yoo, Hye Hyun; Kim, Hyun Young; Kang, Tak Lim; Hwang, Gwi Seo; Park, Jeong Hill (PHARMACEUTICAL SOC KOREA, 2006)
In our efforts to discover novel phytoestrogens to treat menopausal symptoms, eleven furanocoumarins were isolated from Angelica dahurica and tested for their estrogenic activity on the Ishikawa cell line. Among the compounds tested, 9-hydroxy-4-methoxypsoralen and alloisoimperatorin showed strong abilities to induce alkaline phosphatase (AP) with EC50 values of 1.1 and 0.8 mu g/mL, respectively, whereas the other nine furanocoumarins were weakly or only slightly active.
Keywords: CANCER; COUMARINS